RANCANG BANGUN SISTEM INFORMASI SAPU BERSIH PUNGUTAN LIAR DI KABUPATEN CIAMIS MENGGUNAKAN METODE EXTREME PROGRAMMING - Hartono, Rudi (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Abstract. Illegal levies are a troubling problem in various sectors of Indonesian society, including in Ciamis District. Although the Illegal Levy Task Force has been formed, obstacles in reporting cases are a serious challenge. This research aims to design an Information System for the Clean Sweep of Illegal Levies (SIBERLI) in Ciamis District using Extreme Programming (XP). XP was chosen because it emphasizes team collaboration and adaptability, according to the needs of handling complex illegal levy cases. The results of Black-box Testing and User Acceptance Testing (UAT) show the system is worth 100% and the system works efficiently based on the quality of the solution to solve the problem. It is hoped that SIBERLI can help facilitate the public in reporting cases of illegal levies, increase the effectiveness of handling, and increase local revenue.